Investigation and Selection of Overseas Suppliers with Emphasis on Risk Indicators in Iran - Ajamhasani, Ehsan; Garousianb, Vahid Sanavi (International Review of Management and Marketing, 2017)
The present study was done with aimed to investigate and select overseas suppliers with emphasis on risk indicators in Iran’s manufacturing companies in Khorasan province. This research was applied in terms of its purpose and is also part of descriptive-analytical research. A questionnaire was used to collect information. Given that contracting or contracting by low-cost overseas suppliers is an attractive topic in the global economy, Unfortunately, these decisions are made without due consideration to the requirements, market demand and proper delivery system, which usually results in bad results. Determining the risk factors affecting the supply chain of a manufacturing company, determining the decision making options for adopting its purchasing or manufacturing policies, and how to interact with the company’s experts can help companies make better decisions about making or purchasing final products or parts. By reviewing the literature of research and using expert opinions, a list of effective criteria for the assessment and selection of overseas suppliers was identified in five general categories (demand, supply, infrastructure, regulatory, environmental, and catastrophic risks). According to the results of this study, among the main criteria, the risk of supply has the highest weight, so it is more important than other major criteria. Keywords: Risk Indicators, Demand Risks, Supply Risk, Infrastructure Risk, Regulatory and Environmental Risks JEL Classifications: M30, M31